Hip Pain while using lower extremity joints is associated with sleep disturbances in elderly Caucasian women: the Study of Osteoporotic Fractures - Parimi, Neeta (2012)
OBJECTIVE: To evaluate sleep quality in women with hip pain due to daily activities involving the lower extremity joints. METHODS: We evaluated the association of the the Western Ontario MacMaster Osteoarthritis Index (WOMAC) hip pain severity score, with objective sleep measures, obtained by wrist actigraphy, in 2225 Caucasian women ≥ 65 years from the Study of Osteoporotic fractures study. RESULTS: Women had an increased odds of spending ≥1.5 hours awake after sleep onset (WASO) (OR: 1.28, 95% CI: 1.11–1.50) for every 5 units increase in hip pain score after adjustment for all covariates. Resting hip pain was the strongest predictor of sleep fragmentation (OR: 2.0, 95%CI 1.47–2.73), however standing pain was associated with higher WASO independent of pain while in bed (OR: 1.41, 95% CI: 1.07–2.01). Sleep disturbances increased significantly after the first two hours of sleep in women with severe hip pain compared to those without hip pain (1.4 ± 0.47 minutes per hour sleep p=<0.003). Similar associations were observed for long wake episodes greater than 5 minutes. There were no associations with daytime napping, sleep latency, sleep efficiency and total sleep minutes and WOMAC hip pain. CONCLUSION: Fragmented sleep was greater in women with hip pain compared to those without hip pain. However, fragmented sleep in women with severe hip pain compared to those without hip pain was unchanged until after the first two hours of sleep. Further investigation, such as pain medications wearing off over time, or prolonged periods of inactivity decreasing the pain threshold are warranted.